Formal synthesis of (+)-didemniserinolipid B employing a Pd-mediated 6-endo selective alkynediol cycloisomerization - Ramana, C. V.; Induvadana, Boddeti (Tetrahedron Letters, 2009)
Herein, we describe a concise assembly of central 6,8-dioxabicyclo[3,2,1]octane core of didemniserino-lipid by employing a Pd-mediated alkynediol cycloisomerization and a formal total synthesis of didemniserinolipid (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Alkynol cycloisomerization; Bridged bicyclic ketal; Didemniserinolipid; Yamaguchi oxirane alkyne coupling; Zipper reaction

Influence of electronic factors on pd-mediated cycloisomerization: a systematic investigation of competitive 6-exo-dig versus 7-endo-dig cyclizations of sugar alkynols - Ramana, C. V.; Induvadana, Boddeti; Srinivas, Burgula; Yadagiri, Kommagalla; Deshmukh, Madhusudhan N.; Gonnade, Rajesh G. (Tetrahedron, 2009)
Pd-mediated cycloisomerization of 3-C-propargyl-ribo- and allofuranose derivatives was investigated in detail to understand the influence of electronic factors on the regioselectivity (6-exo- vs 7-endo) of alkynol cycloisomerization leading either to a six- or seven-membered ring. In general, the 6-exo-dig mode of cyclization is facile and is independent of electronic factors. With some of the alkynols, a regioselective (7-endo?) hydration of the alkyne unit was observed and this has been attributed to the participation of C(3)-OH. When the C(3)-OH was protected as its benzyl ether, cycloisomerization of these alkynols occurred exclusively in a 6-exo-dig mode resulting in the corresponding [3.2.1]-bicyclic ketals. Additional control experiments conducted were in support of the participation of C(3)-OH in regioselective alkyne hydration. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Alkynol cycloisomerization; Bridged bicyclic ketal; Palladium; Sonogashira coupling; Sugar alkynol

Metal-mediated alkynediol cycloisomerization: first and second generation formal total syntheses of didemniserinolipid B - Das, Shyamsundar; Induvadana, Boddeti; Ramana, C. V. (Tetrahedron, 2013)
A formal total synthesis of didemniserinolipid B was developed by employing a regioselective metal-mediated 6-endo-dig alkynol-cycloisomerization reaction. Two routes for the synthesis of key Burke's intermediate have been developed. Our initial approach involved the introduction of a C-17-allcynol followed by Pd-mediated cycloisomerization and then coupling with the serinol unit prior to the introduction of an alpha,beta-unsaturated ester unit through selective oxidation of 1 degrees-OH followed by a two-carbon Wittig homologation. Alternatively, the second generation strategy featuring the serinol coupling with the C-17-alkynol followed by alkyne addition to the epoxide and subsequent Au-mediated cycloisomerization of an acetonide protected alkynediol unit has been executed. This approach has avoided several late stage protection-deprotection events. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Alkynol-cycloisomerization; Bicyclic ketal; Gold catalysis; Palladium catalysis; Zipper reaction